Schema activation strategy in reading comprehension to improve student's interest - Rizky Hidayatullah; Andika Ari Saputra; Dian Risky Amalia; Umar Alfaruq A. Hasyim (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2019)
This research is aimed to improve the reading comprehension through schema activation strategy. Classroom Action Research (CAR) was conducted in two cycles and each cycle consisted of four phases. They were planning, acting, observing, and reflecting. The subjects of the study were 34 students of Class VIII A of SMP Muhammadiyah 1 Godean. There were two forms of data in this study. The qualitative data were collected through observation and interview. The data were presented in the form of field notes and interview transcripts. Then, the quantitative data were collected through Pre-test, Posttest I, and Posttest II. In reference to the application of the two cycles, the results of the research revealed that use of schema activation strategy successfully improved the students